Comparison of myocardial remodeling between cryoinfarction and reperfused infarction in mice - Duerr, Georg D.; Elhafi, Naziha; Bostani, Toktam; Ellinger, Jörg; Swieny, Louay; Kolobara, Elvis; Welz, Armin; Dewald, Oliver (Journal of Biomedicine and Biotechnology, 2011)
Myocardial infarction is associated with inflammatory reaction leading to tissue remodeling. We compared tissue remodeling between cryoinfarction (cMI) and reperfused myocardial infarction (MI) in order to better understand the local environment where we apply cell therapies. Models of closed-chest one-hour ischemia/reperfusion MI and cMI were used in C57/Bl6-mice. The reperfused MI showed rapid development of granulation tissue and compacted scar formation after 7 days. In contrast, cMI hearts showed persistent cardiomyocyte debris and cellular infiltration after 7 days and partially compacted scar formation accompanied by persistent macrophages and myofibroblasts after 14 days. The mRNA of proinflammatory mediators was transiently induced in MI and persistently upregulated in cMI. Tenascin C and osteopontin-1 showed delayed induction in cMI. In conclusion, the cryoinfarction was associated with prolonged inflammation and active myocardial remodeling when compared to the reperfused MI. These substantial differences in remodeling may influence cellular engraftment and should be considered in cell therapy studies. Copyright © 2011 Georg D. Duerr et al.
CRIS-Team Scopus Importer:2022-05-03